Pengaruh Pelatihan, Pengembangan Sumber Daya Manusia dan Budaya Organisasi Terhadap Kinerja Karyawan Pimpinan pada Kantor Regional III PT. Perkebunan Nusantara IV Kota Pekanbaru - Salsabila, Niki; Sulistyandari; Ayu Nofirda, Fitri (PT. Karya Inovatif Nusantara, 2024)
This research aims to determine the influence of training, human resource development, and organizational culture on the performance of managerial employees. This study uses a quantitative method and a Likert scale for measurement. The population used in this research consists of managerial employees at the regional office III of PT. Perkebunan Nusantara IV in Pekanbaru City. The sample of this study is 108 respondents. Data collection was carried out through questionnaires distributed to managerial employees of PT. Perkebunan Nusantara IV in Pekanbaru City using a purposive sampling technique. Data testing employs validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and termination tests with the help of SPSS 26 software. The results of this study indicate that training has a positive and significant effect on the performance of managerial employees, human resource development has a positive and significant effect on the performance of managerial employees, and organizational culture has a positive and significant effect on the performance of managerial employees